1999
DOI: 10.1055/s-2007-978760
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Serum Albumin and Bone Mineral Density in Postmenopausal Women and in Patients with Hypoalbuminemia

Abstract: Some discrepancies exist about the relationship between serum albumin level and the pathogenesis of osteoporosis; moreover, most of the studies available have especially concerned patients with osteoporosis, often associated with fractures. Our study, therefore, aims to investigate the presence of a relationship between serum albumin level and bone mineral density in a group of healthy women (n=650; mean age 59.0 +/- 7.4 years) who voluntarily underwent screening for osteoporosis only because they were menopau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 11 publications
1
11
1
Order By: Relevance
“…Hypoalbuminemia has been reported in humans with osteopenia [52] and has been associated with increased disease severity and higher mortality in both human and canine patients with inflammatory bowel disease [53][56]. Additionally, low serum albumin has been found to be a risk factor for low bone mineral density, a recognized complication of Crohn’s disease in humans [57].…”
Section: Discussionmentioning
confidence: 99%
“…Hypoalbuminemia has been reported in humans with osteopenia [52] and has been associated with increased disease severity and higher mortality in both human and canine patients with inflammatory bowel disease [53][56]. Additionally, low serum albumin has been found to be a risk factor for low bone mineral density, a recognized complication of Crohn’s disease in humans [57].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that these factors are causal, the common pathogenic pathway being malnutrition or low physical activity, though it has been suggested that atherosclerosis is a consequence of hyperparathyroidism [22]. Hypoalbuminemia in systemic disease is related to osteopenia [23] as is diabetes [2], but atherosclerosis and renovascular disease have not previously been associated. Acidosis is well recognised as a cause of bone loss [24] and bicarbonate therapy can improve bone metabolism [25].…”
Section: Discussionmentioning
confidence: 99%
“…However, data on the exact reason remains scant. Previous studies showed lower albumin level was associated with low BMD and recurrent falls after low-energy injury [ 36 , 37 ]. In addition, we hypothesize that euthyroid sick syndrome (ESS) might be responsible for reoperation in patients with hypoalbuminemia.…”
Section: Discussionmentioning
confidence: 99%